Economic and image impacts of summer Olympic games in tourist destinations: a literature review - Luciana Brandão Ferreira; Marina Toledo de Arruda Lourenção; Janaina de Moura Engracia Giraldi; Jorge Henrique Caldeira de Oliveira (Tourism & Management Studies)
This article aims to verify in the literature related to the Summer Olympics the main economic and image implications for the destination hosting it. A qualitative exploratory research was carried out with the survey of scientific articles of the last twenty-five years in five different databases. The studies indicate economic and image gains and losses from hosting the games. As positive aspects, most of the studies mention those coming from Olympic spending that provided long-term gains for the resident population in the host locality and related to tourist activity. The most cited negative aspects are related to investments that generated benefits only in the short term or lack of investment in infrastructure. It is concluded that the preparation and implementation processes in each country are too different for the results to be uniform. In addition, the diverse methodological aspects of the articles also influence their results.